TRANSLATION TECHNIQUES ON INDONESIAN SWORN TRANSLATOR’S LEGAL TEXTS TRANSLATION - Aris Wuryantoro; H.D. Edi Subroto; M.R. Nababan (Universitas PGRI Madiun, 2014)
Legal translation is the transferring the meaning from source language text into target language which not only consists of language system but also legal system. This research aims to analyze the translation techniques used by the Indonesian sworn translators in translating legal texts from English into Indonesian. This research uses descriptive qualitative method. Data obtained through content analysis on translations of the Indonesian sworn translators containing Certificate of Live Birth, Certificate of Marriage, Principles Statement of Terms and Conditions. The result of the research reveals: a) single translation technique dominates the translation technique in translating legal and law scientific texts from English into Indonesian obtains (66,67%) data consisting of 10 variants (literal, amplification, recognized, reduction, borrowing, modulation, transposition, adaptation, colque, and description); b) couplet translation technique (32,%) data consisting of 16 variants (literal and borrowing, literal and recognized equivalent, literal and reduction, literal and adaptation, literal and amplification, literal and transposition, literal and modulation, literal and colque, borrowing and amplification, literal and description, borrowing and modulation, borrowing and adaptation, borrowing and transposition, modulation and colque, reduction and colque, and reduction and adaptation), and triplet translation technique (1,19%) data consisting of 4 variants (literal + borrowing + modulation, literal + amplification + transposition, literal + amplification + borrowing, and literal + transposition + reduction). Researcher concludes that translation technique of legal texts from English into Indonesian conducted by Indonesian sworn translators contains three kinds of translation techniques, i.e. single translation technique, couplet translation technique, and triplet translation technique with 30 variants